Pemanfaatan Layanan Sistem Informasi Digital Perpustakaan (Sinditaka) oleh Mahasiswa di Universitas Medan Area - Devi Ramadhani; Irwansyah; Ismail (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study discusses the utilization of the Library Digital Information System Service (SINDITAKA) by final semester students at Medan Area University. This study focuses on the use of digital information systems to facilitate library catalog searches and improve the quality of information services. The method used is qualitative research with a descriptive approach. The informants in this study were the head of the Library and Archives at Medan Area University. Data were collected from documents, interviews, field notes, and observations. The results of the study indicate that SINDITAKA provides access to various digital collections, including printed books, e-books, and e-journals, which make it easier for students to find information.